Nigerian Public Sector and the Challenge of Workers’ Productivity: An Evaluation - Shimawua, Dominic; Sunday, Adejoh (NIU Journal of Social Sciences; Vol 4 No 2 (2018): KIU Journal of Social Sciences, Vol. 4 No. 2, June 2018, 2018)
Productivity means the continuing improvement of the firm management performance in the use of resources and though the operations it is conducted. However the paper highlights those factors responsible for low productivity among Nigerian workers. The paper focus on those means that will be applied to get workers committed to tier work using effective national tool to enhance and increase productivity level of the public sector in Nigeria. The paper conclude that productivity is the lifeblood of our economy and key to high standard of living. Productivity growth is important for the wellbeing of future generation.   It is only by productivity that the real national wealth of a country can increase. The paper therefore, recommended that it is necessary that organization should set out their productivity goal before they even embark on production and the goals must be realistic, specific, comprehensive and meaningful. Keywords: Evaluation, Factors Responsible, Low Productivity, Workers, Public Sector